Programa de desarrollo del plan motor general y segmentario, como preparación del proceso de lecto. - Cruz Espinoza, Estefanía Elizabeth (2016)
This systematization of psychomotor experience developments a program for children from 8 to 10 years of the Educational Institution named "San Patricio" which belongs to the Salesian Street Children Project Foundation. To get an appropriate registration of systematization of experience workshops psychomotor some workshops are implemented, these activities encourage the development of general and segmental motor plan and the graphomotor reeducation, as a premise to facilitate the process of reading and writing in children, in a period of five months from February to July 2016. The pre-test and post-test results used in quantitative and qualitative questionnaire form C.E.P.A. These are applied to the first cycle teacher, a significant change is shown in each of their areas. The Skill Test Powertrain called Ozeretsky contains some tests that have been successfully overcome. Finally it is also shown the qualitative analysis of the dictation area test T.A.L.E. The application program can check a significant improvement in Psychomotor and graphomotor areas, the results of the final test were much more positive comparing with the initial tests taken.